ANALISIS TREND PENDIDIKAN MULTIKULTURAL DALAM KONTEKS PENDIDIKAN ISLAM DI SMA : SYSTEMATIC LITERATURE REVIEW - Faturrahman, Muhammad Aji; Afriyadi, Muhammad Muchsin; Romlah, Listiyani Siti; Baharudin, Baharudin; Sabira, Qonita (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The diversity of cultures, religions, and ethnicities in Indonesia requires the education system to integrate multicultural values, especially in the context of Islamic Education at the Senior High School (SMA) level. This study aims to examine the trends and developments in the implementation of multicultural education in Islamic Religious Education (PAI) learning through the Systematic Literature Review (SLR) approach. Data were collected from scientific articles published in the period 2019–2024, which were indexed in international databases such as Scopus, Taylor & Francis, and Google Scholar using Publish or Perish. The selected articles were analyzed using the PRISMA protocol, including the processes of identification, screening, and thematic analysis. The results of the study indicate that multicultural education in the context of PAI in senior high schools tends to experience increased attention, with the main focus on strengthening the values ??of tolerance, respect for differences, and religious moderation. However, challenges were also found in its implementation, such as local cultural resistance and limited teacher understanding. The conclusion of this study emphasizes the need to strengthen the curriculum, teacher training, and education policies that support the mainstreaming of multicultural values ??in Islamic education at the senior high school level. ABSTRAKKeberagaman budaya, agama, dan etnis di Indonesia menuntut sistem pendidikan untuk mengintegrasikan nilai-nilai multikultural, khususnya dalam konteks Pendidikan Islam di jenjang Sekolah Menengah Atas (SMA). Penelitian ini bertujuan untuk mengkaji tren dan perkembangan implementasi pendidikan multikultural dalam pembelajaran Pendidikan Agama Islam (PAI) melalui pendekatan Systematic Literature Review (SLR). Data dikumpulkan dari artikel ilmiah yang dipublikasikan dalam rentang waktu 2019–2024, yang terindeks di basis data internasional seperti Scopus, Taylor & Francis, dan Google Scholar menggunakan Publish or Perish. Artikel yang terpilih dianalisis menggunakan protokol PRISMA, mencakup proses identifikasi, penyaringan, dan analisis tematik. Hasil penelitian menunjukkan bahwa pendidikan multikultural dalam konteks PAI di SMA cenderung mengalami peningkatan perhatian, dengan fokus utama pada penguatan nilai toleransi, penghargaan terhadap perbedaan, dan moderasi beragama. Namun demikian, ditemukan pula tantangan dalam implementasinya, seperti resistensi budaya lokal dan keterbatasan pemahaman guru. Kesimpulan dari studi ini menegaskan perlunya penguatan kurikulum, pelatihan guru, dan kebijakan pendidikan yang mendukung pengarusutamaan nilai multikultural dalam pendidikan Islam di tingkat SMA.